PERSEPSI MASYARAKAT DESA PEDULI GAMBUT PADA KEBIJAKAN RESTORASI LAHAN GAMBUT DI KABUPATEN KUBU RAYA: Perceptions of Peat Care Village Community on Peatland Restoration Policy in Kubu Raya District - Yurisinthae, Erlinda; Kurniadi, Dedi; Yusra, Abdul Hamid A. (AgriPeat, 2023)
During this time peatlands were discussed related to forest and land fires so that presidential regulation No. 1 of 2016 concerning peat restoration agency (BRG) was issued. The initial study of BRG on the development status of villages in the bergambut area shows that most villages are in the status of villages are very left behind or villages are left behind, so the peat care village (DPG) approach is used. The purpose of the study is: analyzing the perception of peat care village communities in Kubu Raya Regency on peatland restoration policies and analyzing factors that affect community participation in BRG programs and activities. The research location is Kubu Raya Regency. The population of this study is a community in DPG Sungai Nipah. The number of samples as many as 32 respondents and sampling was done using snowballing sampling. The variables studied are: characteristics of respondents, characteristics of peatland restoration policies, community perceptions, opinions/responses that are views given by the community on peat restoration policies, knowledge, and attitudes. To analyze factors that affect community participation in BRG programs and activities are used Logit Regression. Overall, respondents' attitudes towards BRG programs and activities were in the positive to very positive range. The variables of gender, perception and variable experience of trying to exert a significant partial influence on participation in BRG programs and activities. To improve the positive perception of the community, there is a need for assistance efforts from all community institutions in rural areas. Paludiculture cultivation techniques and using creative economic development strategies on peat swamplands with Green Circular Economy Consep can be an alternative to BRG programs and activities.